Mitochondrial Deoxyguanosine Kinase Regulates NAD+ Biogenesis Independent of Mitochondria Complex I Activity - Sang, Lei; He, Ying-Jie; Kang, Jiaxin; Ye, Hongyi; Bai, Weiyu; Luo, Xiao-Dong; Sun, Jianwei (Frontiers in Oncology, 2020)
Overexpression of DGUOK promotes mitochondria oxidative phosphorylation and lung adenocarcinoma progression. However, the role and mechanism of DGUOK in regulation of mitochondria function and lung cancer progression still poorly understood. Here we demonstrated that DGUOK regulated NAD+ biogenesis. Depletion of the DGUOK significantly decreased NAD+ level. Furthermore, knockout of the DGUOK considerably reduced expression of the NMNAT2, a key molecule controlling NAD+ synthesis, at both mRNA and protein levels. Ectopic expression of the NMNAT2 abrogated the effect of knockdown of DGUOK on NAD+. Notably, this regulation is independent of DGUOK -mediated mitochondria complex I activity. We also showed that NMNAT2 was highly expressed in lung adenocarcinoma and negatively correlated with the patient overall survival. Our study suggested that DGUOK regulates NAD+ in a NMNAT2 dependent manner and DGUOK-NMNAT2-NAD+ axis could be a potential therapeutic target in lung adenocarcinoma.